Is soluble protein mineralisation and protease activity in soil regulated by supply or demand?. (November 2020) - Greenfield, Lucy M.; Hill, Paul W.; Seaton, Fiona M.; Paterson, Eric; Baggs, Elizabeth M.; Jones, Davey L.
Abstract: Protein represents a major input of organic matter to soil and is an important source of carbon (C) and nitrogen (N) for microorganisms. Therefore, determining which soil properties influence protein mineralisation in soil is key to understanding and modelling soil C and N cycling. However, the effect of different soil properties on protein mineralisation, and especially the interactions between soil properties, are poorly understood. We investigated how topsoil and subsoil properties affect protein mineralisation along a grassland altitudinal (catena) sequence that contained a gradient in soil type and primary productivity. We devised a schematic diagram to test the key edaphic factors that may influence protein mineralisation in soil (e.g. pH, microbial biomass, inorganic and organic N availability, enzyme activity and sorption). We then measured the mineralisation rate of 14 C-labelled soluble plant-derived protein and amino acids in soil over a two-month period. Correlation analysis was used to determine the associations between rates of protein mineralisation and soil properties. Contrary to expectation, we found that protein mineralisation rate was nearly as fast as for amino acid turnover. We ascribe this rapid protein turnover to the low levels of protein used here, its soluble nature, a high degree of functional redundancy in the microbial community and microbial enzyme adaptation to their ecological niche. Unlike other key soil N processes (e.g. nitrification, denitrification), protease activity was not regulated by a small range of factors, but rather appeared to be affected by a wide range of interacting factors whose importance was dependent on altitude and soil depth [e.g. above-ground net primary productivity (NPP), soil pH, nitrate, cation exchange capacity (CEC), C:N ratio]. Based on our results, we hypothesise that differences in soil N cycling and the generation of ammonium are more related to the rate of protein supply rather than limitations in protease activity and protein turnover per se . Highlights: Protein mineralisation rates differed along a grassland altitudinal gradient. Effect of soil parameters on protein breakdown rates were modelled. Protein mineralisation rate was nearly as fast as for amino acid mineralisation. Protein mineralisation had weak relationships with many interacting edaphic factors. Interactions between edaphic factors are more important than individual effects on protein mineralisation.